Fabrication and performance of mini SiC/SiC composites with an electrophoresis-deposited BN fiber/matrix interphase. Issue 5 (May 2022) - Xu, Bin; Yang, Huiyong; Luo, Ruiying; Wang, Lianyi; Huang, Juntong; Chen, Dian
Abstract: The feasibility of fabricating a BN matrix/fiber interphase of SiC/SiC composites via electrophoresis deposition (EPD) was investigated based on the simplicity and non-destructiveness of the process and the excellent interfacial modification effects of BN. The BN suspension and SiC fiber surface properties were both adjusted to generate suitable conditions for the EPD process of the BN interphase. Next, the deposition dynamics and mechanism were studied under different deposition voltages and time, and the relationship between the deposition morphology of the BN interphase and mechanical properties of the fabricated mini SiC/SiC composites were also discussed. After oxidation at high temperature (600–1000 ℃), the mechanical properties of the mini SiC/SiC composites were studied to verify the oxidation resistance effect of the EPD-deposited BN interphase, whose oxidation resistance mechanism was briefly analyzed as well. Graphical Abstract: ga1